IMPLEMENTATION OF DISCOVERY MODELS FOR BUILDING SKILLS OF HISTORICAL COMPREHENSION ON HISTORY OF STUDENTS IN THE SRIJAYANEGARA HIGH SCHOOL IN PALEMBANG - Wirda Wirda; Hudaidah Hudaidah (Sriwijaya University Learning and Education International Conference, 2018)
This paper is a field study, in implementing discovery learning models to build historical comprehension skills in the history subjects of Srijaya Negara High School students in Palembang. The problems proposed are: (a). How to improve the historical comprehension skills of students in historical subjects? The research carried out is a field study in order to improve the historical comprehension of students specifically in finding opinions with the discovery model. Through this research it was found that there was an increase in students' skills in expressing opinions, especially in the form of historical comprehension.